Nasolabial Cyst: A Case Report with Ultrasonography and Magnetic Resonance Imaging Findings - Ali Ocak; Suayip Burak Duman; Ibrahim Sevki Bayrakdar; Binali Cakur (Hindawi Limited, 2017)
Nasolabial cysts are uncommon nonodontogenic lesions that occur in the nasal alar region. These lesions usually present with asymptomatic swelling but can cause pain if infected. In this case report, we describe the inadequacy of conventional radiography in a nasolabial cyst case, as well as the magnetic resonance imaging (MRI) and ultrasonography (US) findings in a 54-year-old female patient.